ENSINO HÍBRIDO E EDUCAÇÃO AMBIENTAL: UMA INTERSECÇÃO POSSÍVEL (Revista Contexto & Educação, 2020)
This research presents theoretical-methodological contributions to the teaching of Environmental Education (EE) from the perspective of Blended Learning. The objective of this study was to investigate whether the organization of didactic activity, in the Blended Learning model, provides adequate conditions for the awakening of an ecological subject based on Critical Environmental Education. The research data were organized and interpreted through the Content Analysis and showed that the actions of EE made it possible to conduct a new perspective of the students in relation to the environment, denoting a desire for change and environmental transformation, however, it highlighted the need to broaden the EE discourse that considers social issues; also showed that technologies were allied in the teaching process, stimulating learning and culminating in actions of autonomy and criticality on the part of students.